2020
DOI: 10.3390/nu12072159
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Antitumor Efficacy of Hizikia fusiforme Celluclast Extract against Bladder Cancer

Abstract: Various physiological benefits have been linked to Hizikia fusiforme (HF), an edible brown seaweed. Here, fucose-containing sulfated polysaccharides were extracted from celluclast-processed HF (SPHF) and their antitumor efficacy against bladder cancer was evaluated in vitro and in vivo. SPHF possesses high sulfated polysaccharide and fucose contents and free radical scavenging activities compared to those of celluclast-processed HF extracts (CHF). SPHF inhibited bladder cancer EJ cell proliferation via G1-phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…In addition, SPHF inhibited migration and invasion of EJ cells by reduction of the transcription factor related matrix metalloprotein (MMP-9) expression. 102 Fan et al studied the antitumor effect of S. f usiforme polysaccharide on nasopharyngeal carcinoma (NPC) and its potential mechanism on spleen lymphocytes. The outcome showed that the polysaccharides remarkably suppressed the growth of human nasopharyngeal cancer cells (CNEs) in vitro and improved the levels of serum cytokines and immunoglobulin M (IgM) in mice.…”
Section: Antitumor Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, SPHF inhibited migration and invasion of EJ cells by reduction of the transcription factor related matrix metalloprotein (MMP-9) expression. 102 Fan et al studied the antitumor effect of S. f usiforme polysaccharide on nasopharyngeal carcinoma (NPC) and its potential mechanism on spleen lymphocytes. The outcome showed that the polysaccharides remarkably suppressed the growth of human nasopharyngeal cancer cells (CNEs) in vitro and improved the levels of serum cytokines and immunoglobulin M (IgM) in mice.…”
Section: Antitumor Activitymentioning
confidence: 99%
“…Many reports indicate that the active substances in S. fusiforme have antitumor effects. , Kim et al isolated saringosterol acetate (SSA) from S. fusiforme and established the effect of SSA on tumor growth and metastasis in an adult zebrafish human hepatocellular carcinoma (HCC) xenotransplantation model . The results showed that SSA affects survival rate, alpha-fetoprotein (AFP) production, the level of the factors related to tumor growth and metastasis via regulating phosphoinositide 3-kinase (PI3K)/serine-threonine kinase (AKT)/mammalian target of rapamycin (mTOR) and transforming growth factor-beta (TGF-β)/Smad pathways .…”
Section: Bioactivities Of S Fusiformementioning
confidence: 99%
See 1 more Smart Citation
“…In vitro Inhibited the growth of U87MG cell line [129] Carrageenan extract from Gigartina pistillata inhibits cell growth in colorectal cancer stem cells with an IC 50 value of 1 µg/mL [125]. Moreover, Hizikia fusiforme inhibited EJ tumor growth both in vivo and in vitro through G1-phase cell cycle arrest by downregulating cyclins and cyclin-dependent kinases (CDKs), as well as by inhibiting the expression of MMP-9 by downregulating NF-κB, AP-1, and Sp-1 [122]. In addition, seaweed extract also exhibited potent anticancer activity against hepatocellular carcinoma (HCC) cell lines [123], the U87MG cell line [129], and sarcoma 180 ascites tumor cells both in vitro and in vivo [126].…”
Section: Sulfated Heterorhamnansmentioning
confidence: 99%